An analysis of graduate dissertations and papers related to visual arts area at science and art centers between the years of 2007-2017 - Usal, Yelda; Buyurgan, Serap (Horizon Research Publishing, 2018)
In the study, the data for the field of visual arts in BILSEM have been revealed by studying postgraduate theses and articles related to the field of Visual Arts given in Science and Art Centers in between 2007-2017. In the research, the document was examined with the scanning model. In the scope of the research, it has been scanned from Google Scholar with keywords such as "BILSEM", "Art Education", "Visual Arts Education" and "Linear Development" in the YÖK database thesis and related theses and articles between the years 2007-2017 examined in terms of type, subject, sample, university and institute, national/ international, thesis method, data collection tools. In laser scanning, Visual Arts given in BILSEM in 2007-2017 years in Turkey related to Education "Science and Art Centers", "BILSEM", "Arts Education", "Visual Arts Education" and "Linear Development" screening using keywords according to the results of 6 theses (4 Master, 2 PhD) and 8 articles have been found. According to the results of the study, it is seen that there are no postgraduate thesis and articles about Visual Arts Education given in BILSEMs in 2009, 2010 and 2011, and studies have been intensified in between 2012-2017. © 2018 by authors, all rights reserved.
Keywords: Ability; Fine arts high schools; Science and art centers; Superior intelligence; Visual arts